MENINGKATKAN KEMAMPUAN ESSAY WRITING DENGAN MENERAPKAN METODE COLLABORATIVE WRITING PLUS PADA MAHASISWA DENGAN LEVEL ENGLISH PROFICIENCY YANG BERBEDA - Wigati, Fikri Asih (Majalah Ilmiah SOLUSI, 2015)
This research investigated the use of Collaborative Writing Plus technique in students’ writing ability across different proficiency levels. The research was a classroom action research to find out whether the technique improved the students’ writing ability or not. The Classroom Action Research includes four main steps:planning, acting, observing, and reflecting, conducted in three cycles. The subject of the study was fourth semester students who study in English Education Program in one of the universities in Karawang. The instruments of this study were: students’ writing tests, observation checklist, students’ journal. The findings showed that the technique improved the students’ writing ability in five aspects which include content, organization, vocabulary, grammar, and mechanic in writing in the descriptive text.It is finally suggested that English teachers can use the technique to handle a class comprising students with different language proficiency levels. The other researchers are invited to conduct further research related to other English skills . Keywords : Collaborative Writing Plus Technique, Language Proficiency Levels, Writing Aspects